Enhanced death ligand-induced apoptosis in cutaneous SCC cells by treatment with diclofenac/hyaluronic acid correlates with downregulation of c-FLIP - Fecker, Lothar Friedrich; Stockfleth, Eggert; Braun, Frank K.; Rodust, Paul M.; Schwarz, Constanze; Köhler, Anja; Leverkus, Martin; Eberle, Jürgen (The journal of investigative dermatology, 2010)
Actinic keratosis (AK) occurs on sun-exposed skin and may progress to invasive squamous cell carcinoma (SCC). As for its topical treatment, diclofenac/hyaluronic acid (HA) has been recently approved. The NSAID diclofenac is an inhibitor of COX-2; however, its mode of action in cutaneous epithelial cancer cells is largely unknown. Here, the effects of diclofenac/HA were investigated in relation to death ligand-mediated apoptosis (TNF-α, TRAIL, and CD95 activation). Whereas diclofenac/HA only moderately induced apoptosis by itself, it resulted in pronounced enhancement of death ligand-mediated apoptosis in sensitive SCC cell lines (3/4). Apoptosis was associated with activation of initiator caspases of the extrinsic pathway (caspase-8/caspase-10). Furthermore, death ligand and diclofenac/HA-mediated apoptosis were blocked by the same caspase inhibitors, indicating related pathways. The proapoptotic effects of diclofenac/HA appeared independent of the p53 pathway. Also, upregulation of death receptors appeared less important; however, strong downregulation of c-FLIP isoforms was seen after diclofenac/HA treatment. The crucial role of c-FLIP was proven through overexpression and knockdown experiments. Thus, induction of apoptosis appears to be highly characteristic of the mode of action of diclofenac/HA, and the therapeutic effect may be related to sensitization of neoplastic keratinocytes for death ligand-induced apoptosis.
Gesehen am 15.08.2023